Odpowiedzi

2010-01-24T17:47:47+01:00
Najlepsza Odpowiedź!
2010-01-24T17:49:29+01:00
(tg²α - 1)/(tg²α + 1) =

= (sin²α/cos²α - 1) / (sin²α/cos²α + 1) =

= ((sin²α - cos²α) / cos²α) / ((sin²α + cos²α) / cos²α) =

= (sin²α - cos²α) / (sin²α + cos²α) =

= sin²α - cos²α

bo sin²α + cos²α = 1 (jedynka trygonometryczna)
2010-01-24T17:51:50+01:00
Sin²α - cos²α = (tg²α - 1)/(tg²α + 1)
tgα = sinα/cosα
prawa strona równania =
(tg²α - 1)/(tg²α + 1) = (sin²α/cos²α - 1)/(sin²α/cos²α + 1)=
(sin²α/cos²α - cos²α/cos²α)/(sin²α/cos²α + cos²α/cos²α)=
((sin²α - cos²α)/cos²α)/((sin²α + cos²α)/cos²α)=
(sin²α - cos²α)/(sin²α + cos²α) = sin²α - cos²α =
lewa strona równania